Perception Towards Illness and Health Care System among Chronic Kidney Patients with Hemodialysis - Nurul Adzkia Ghearizky; Tri Murti Andayani; Dwi Endarti; Vo Quang Trung (Journal of Health Economic and Policy Research (JHEPR), 2023)
Chronic kidney disease is still a problem faced by the world of health in Indonesia. The high prevalence of chronic kidney disease has increased every year. The high number of cases of chronic kidney disease causes higher efforts to seek treatment for chronic kidney disease which is influenced by perceptions of disease and perceptions of the health service system. This study aims to determine the illness perception and perception of the service system in chronic kidney patients with hemodialysis at one of the district hospitals in Yogyakarta Province (hospital X). Method: The research method was analytic observational with a cross-sectional approach which was carried out at the hemodialysis polyclinic at hospital X in January-February 2023. The sampling technique used Convenience sampling. Data collection was carried out by direct interviews with respondents using a questionnaire. Data were analyzed using the Kolmogorov-Smirnov test and the Chi-Square test. Result and discussion: The research results obtained a total of 102 respondents. The percentage of respondents with a good illness perception was 66.67% and a good perception of the health service system was 90.19%. Based on the results of the study, it can be concluded that perceptions of disease and perceptions of the health service system for chronic kidney patients with hemodialysis at Hospital X tend to be good. Conclusion: The results of statistical tests showed that there was no relationship between gender, age, duration of chronic kidney disease, education level, and family income on perceptions of disease and perceptions of the health service system at Hospital X, Special Region of Yogyakarta.